2019
DOI: 10.2478/raon-2019-0033
|View full text |Cite
|
Sign up to set email alerts
|

KRAS, NRAS, BRAF, HER2 and microsatellite instability in metastatic colorectal cancer – practical implications for the clinician

Abstract: Background Colorectal cancer is a successful model of genetic biomarker development in oncology. Currently, several predictive or prognostic genetic alterations have been identified and are used in clinical practice. The RAS gene family, which includes KRAS and NRAS act as predictors for anti-epithelial growth factor receptor treatment (anti-EGFR), and it has been suggested that NRAS mutations also play a role in prognosis: patients harboring NRAS alterations have a significantly shorter survival compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 90 publications
3
82
2
2
Order By: Relevance
“…BRAF-mutated CRC is currently receiving attention not only from clinicians, but also basic scientists, and thus numerous reviews have been published [3,[8][9][10][11][12][13][14][15][16]. As a medical oncology team, we would like to highlight BRAF-mutated CRC from the clinician's viewpoint.…”
Section: Introductionmentioning
confidence: 99%
“…BRAF-mutated CRC is currently receiving attention not only from clinicians, but also basic scientists, and thus numerous reviews have been published [3,[8][9][10][11][12][13][14][15][16]. As a medical oncology team, we would like to highlight BRAF-mutated CRC from the clinician's viewpoint.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular markers such as K-Ras, N-Ras, B-Raf, HER2, and MSI play a signi cant role in the disease prognosis in CRC, and hence, analysis of these biomarkers helps in facilitating proper treatment to the needy patients [30]. In our study, all the patients in MSI-H status survived for > 3 years, while 3year OS of patients in MSS status was only 35.0% (P = 0.047).…”
Section: Discussionmentioning
confidence: 58%
“…3A). KRAS and BRAF mutations are valuable clinical biomarkers used to guide CRC patient treatment [37]. In this study, we found that almost all patients with KRAS mutations yielded MSS samples that clustered in the Immunity_L subgroup, whereas the majority of samples with BRAF V600E mutations were MSI samples in the Immunity_H subgroup (Fig.…”
Section: Assessment Of Immune Checkpoint Marker Expression and The Tumentioning
confidence: 68%